Pengaruh Intellectual Capital, Leverage, Dewan Direksi pada Sustainability Reporting: Moderasi Pengalaman Direktur - Muhhamad Azhari Brian Aristya; Lin Oktris (Jurnal Proaksi, 2025)
Main Objective - To analyze the effect of intellectual capital, leverage, and board characteristics on the quality of sustainability reporting with directors’ experience as a moderating variable.Method - A quantitative explanatory approach using secondary data from 30 companies listed on the IDX during 2021–2024, analyzed with panel data regression (E-Views).Main Findings - Directors’ experience does not moderate the relationship between intellectual capital, leverage, and multiple directorships with sustainability reporting. However, intellectual capital, leverage, and directors’ experience directly affect the quality of reporting.Theoretical and Policy Implications - The results highlight the importance of experienced directors in managing intellectual capital and leverage to improve the quality of sustainability reporting.Research Novelty - This study identifies a gap showing that directors’ experience is more effective when combined with intellectual capital, while its moderating role on leverage and multiple directorships is not significant. The contribution lies in offering a new perspective on the combination of leadership and intellectual assets in fostering corporate legitimacy.